What Determines the Dynamic Bank Profitability in a Developing Economy? Evidence from Commercial Banks in China - [YU], [XUEMIN] (2020)
This study exactly focuses on the main determinants that influence the profitability of commercial banks in China, which is measured by three significant variables namely, return on average assets (ROAA), return on average equity (ROAE) and net interest margin (NIM). Bank-specific and macroeconomic determinants are selected to examine bank profitability. Pooled, fixed-effects and random-effects models are used as preliminary assessment methods, eventually, system GMM is built on panel data from 2014 to 2018 for 165 commercial banks of China. Accordingly, from the perspective of bank-specific factors, the results indicate that the credit risk, capital adequacy, size and asset liquidity have a vital impact on the profitability of commercial banks in China. The excessive expansion of bank size will significantly limit the increase in profitability; higher impaired loans will weaken the profitability; asset quality and profitability are significant negative correlation; liquidity and profitability of commercial banks are positively correlated but insignificance. However, the macroeconomic environment has a positive but insignificant influence on commercial banks’ profitability in China overall. On this basis, this research proposes corresponding policy recommendations.